Service Quality Realization Strategy in The Integrated Licensing and Investment Services Agency in Majalengka District - Dewi Maharani; Ummu Salamah; Iwan Satibi (Pasundan Social Science Development, 2020)
This research was started by a phenomenon that indicates the optimal quality of licensing service implemented by the BPPT-PM Majalengka Regency. The strengthening of the problem can be seen from public complaints related to the service process provided by the apparatus. Therefore, the researcher focuses on researching the realization of service quality at BPPT-PM in the MajaLengka District. The purpose of the study, among others; first, to examine and analyze the quality of service, secondly, to examine and analyze the factors that determine and cause the quality of service has not been adequate. Third, reviewing and analyzing alternative strategies for the realization of quality of service to run effectively. While the design of this research analysis using a mixed-methods approach through the sequential explanatory model. The study results found that the realization of the quality of business licensing services at BPPT-PM Majalengka District has not entirely run optimally. The results also found the factors that determine the success of realizing the quality of business licensing services on BPPT-PM Majalengka District, among others; Tangible, Reliable, Responsiveness, Assurance, Empathy. In addition to the five factors, the researcher also found one other factor (another dimension) related to the quality of licensing services at BPPT-PM Majalengka, namely; dimensional synergies. The birth of this dimension, academically, and the findings of a new concept in this dissertation research or often known as a novelty. At the same time, the factors that inhibit the realization of the quality of licensing services in BPPT-PM Majalengka District include limitations of online-based service facilities, limited parking area, uncomfortable waiting room, worship place, and little clean room not yet built a proactive and innovative work culture. Therefore, the empirically generated strategy is in the position of the quadrant to me. This position implies that to realize the quality of licensing services within the BPPT-PM, the Majalengka regency needs new alternative strategies to support the process of realizing the quality of service. While the strategy in question is an aggressive strategy (offensive), a development strategy about the situation is very good because there are forces utilized to seize opportunities that benefit.